Can Agong end Perikatan’s skirting of Parliament? Yes, experts say - Wan Ahmad Fauzi, Wan Husain (The Vibes Dotcom Sdn Bhd, 2021)
The government may continue holding off on reconvening Parliament, but a clause in the federal constitution can force the sitting to be held. According to constitutional expert Datuk Wan Ahmad Fauzi Wan Husain, the powers accorded to the Yang di-Pertuan Agong under the law allow His Majesty to summon MPs for a sitting on a date he sees fit.